Respuesta :

Answer:

see explanation

Step-by-step explanation:

(a)

Given

x² + 10x + 16

Consider the factors of the constant term (+ 16) which sum to give the coefficient of the x- term (+ 10)

The factors are + 2 and + 8, since

2 × 8 = 16 and 2 + 8 = 10, thus

x² + 10x + 16 = (x + 2)x + 8)

---------------------------------------------------

(b)

Given

x² + 7x + 12

Consider the factors of the constant term (+ 12) which sum to give the coefficient of the x- term (+ 7)

The factors are + 3 and + 4, since

3 × 4 = 12 and 3 + 4 = 7, thus

x² + 7x + 12 = (x + 3)(x + 4)

------------------------------------------------------

(c)

Given

x² + 13x + 12

Consider the factors of the constant term (+ 12) which sum to give the coefficient of the x- term (+ 13)

The factors are + 1 and + 12, since

1 × 12 = 12 and 1 + 12 = 13, thus

x² + 13x + 12 = (x + 1)(x + 12)

(X+2) (X+8)
(X+3) (X+4)
(X+1) (X+12)